“Técnica de ELTGOL en futbolistas de 15 a 16 años de edad que asisten a la Unidad Educativa Santo Tomás Apóstol, período marzo-agosto 2016”. - Haro Santos, Ana Francisca (2016)
Total slow expiration with open glottis or better known as ELTGOL is a manual pressure technique which was used in young soccer players of the “Santo Tomas Apostol" School in Riobamba city, from March to August 2016, with the purpose to improve their breathing capacity. In addition this technique was complemented with cardiorespiratory exercises which helped to improve the athletic performance of group because this is not a very common practice and this study pretended to check their effectiveness. The theorical analysis with scientific basis of the independent and dependent variables allowed the researcher to understand the etiology of the problem. This was a field-type research and inductive and deductive methods were used in 33 students who were subjected to periodic evaluations to identify their progress and obtain measurable results. During this process a slight improvement was obtained in the values set by the test "Navette". The population showed satisfactory results allowing to conclude that ELTGOL and cardiorespiratory exercises work well and if application continues as planned best results will be obtained and this will lead to form competitive players and reach the victories athletes and institution hope.